1999
DOI: 10.1177/00220345990780120901
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of Acquired Salivary Pellicle as a Determinant of the Sites of Dental Erosion

Abstract: Dental erosion shows a typical distribution pattern within the dental arches. Tooth protection from erosion by salivary pellicle has been shown in vitro, but the hypothesis that pellicle may differ quantitatively at sites of erosion has not been investigated. This study aimed to determine the thickness of acquired salivary pellicle within the dental arches, investigate the possible relationship of this thickness to the distribution and severity of erosion within the arches, and confirm the protective effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
0
65

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(242 citation statements)
references
References 37 publications
9
168
0
65
Order By: Relevance
“…52 Saliva and pellicle are important factors in protection of tooth substance against acid attack. Amaechi et al 33 and Johansson et al 47 have shown that erosion is usually found in areas of the dental arches that are lacking in pellicle. Increasing salivary flow and hence accumulation of pellicle will, therefore, probably offer protection against erosion.…”
Section: Drink Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Saliva and pellicle are important factors in protection of tooth substance against acid attack. Amaechi et al 33 and Johansson et al 47 have shown that erosion is usually found in areas of the dental arches that are lacking in pellicle. Increasing salivary flow and hence accumulation of pellicle will, therefore, probably offer protection against erosion.…”
Section: Drink Modificationmentioning
confidence: 99%
“…[29][30][31] Addition of fluoride to sports drinks has also been shown to reduce the erosive potential of these, otherwise highly erosive, drinks. 32 Amaechi et al, 33 have shown that xylitol and fluoride have an additive effect in reducing the erosive potential of orange juice in in vitro studies. Larsen, 34 however, showed that the protective effect against erosion of fluoride added to soft drinks was minimal.…”
Section: Fluoridementioning
confidence: 99%
“…Estudos sugerem que as superfícies dos dentes com películas mais finas têm uma resistência menor à dissolução mineral em comparação com as superfícies dos dentes com películas mais espessas (Amaechi et al, 1999;Hannig e Balz, 1999;Khan, 2002). Em indivíduos susceptíveis à erosão dental a película adquirida alterada pode ser um potencial fator de risco que contribui para o desenvolvimento de lesões erosivas Moazzez et al, 2014).…”
Section: Importância Da Saliva Na Erosãounclassified
“…Em relação à erosão dentária, a película adquirida pode proteger por atuar como uma barreira de difusão ou membrana, prevenindo o contato direto entre os ácidos e a superfície dentária, desta maneira reduzindo a dissolução dos tecidos dentários duros (AMAECHI et al, 1999;BALZ, 1999;HANNIG, M. et al, 2004;HARA et al, 2006). Em adição, a película é também uma base para que as bactérias possam aderir sobre a superfície dentária quando entram na cavidade bucal (LENANDER-LUMIKARI; LOIMARANTA, 2000), interferindo, desta maneira, na ocorrência de cárie dentária.…”
Section: Lista De Tabelasunclassified
“…Quadro 1 -Concentração proteica média (µg/mL) utilizando o micro BCA nas amostras de película adquirida (papel ou líquido) coletadas do esmalte ou dentina, em diferentes tempos da formação (10 minutos e 2 horas), após exposição a diferentes tipos de ácidos 57 1995;ROLLA, 1973). A película lubrifica as superfícies dentárias, o que reduz o atrito entre os dentes e a mucosa oral (evita o desgaste), forma uma barreira contra a erosão, serve como um reservatório de eletrólitos para a remineralização e apresenta várias propriedades antimicrobianas (AMAECHI et al, 1999;HANNIG, M., 2002;HARA et al, 2006;JOINER et al, 2008;GROGAN;OPPENHEIM, 2000).…”
Section: Introductionunclassified